2012
DOI: 10.1097/brs.0b013e318241b186
|View full text |Cite
|
Sign up to set email alerts
|

2012 Young Investigator Award Winner

Abstract: Our findings suggest that in obese patients, the distribution of body mass is more predictive of SSI than the absolute BMI and deserves attention in preoperative evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(50 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…The use of subcutaneous drains to prevent dead space or recommending weight loss preoperatively may be effective strategies for preventing SSI. Although the different cutoffs (BMI [30 or BMI [35) or different definitions for obesity were utilized in different studies, the influence of obesity on SSI showed a similar trend. Therefore, weight loss may lower risk of SSI after spinal surgery.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The use of subcutaneous drains to prevent dead space or recommending weight loss preoperatively may be effective strategies for preventing SSI. Although the different cutoffs (BMI [30 or BMI [35) or different definitions for obesity were utilized in different studies, the influence of obesity on SSI showed a similar trend. Therefore, weight loss may lower risk of SSI after spinal surgery.…”
Section: Discussionmentioning
confidence: 75%
“…Although longer operative times were dictated mostly by the surgical complexity of the procedure, they can be mitigated by factors such as the proficiency of the surgeon and the operation methods [32]. The proper methods, which can minimize tissue necrosis and decrease infection rates, include releasing the tension on self-retractors often [49] and frequent irrigation of the Number of spinal levels operated 229 [1,50] 3 9 [ 28,35] Surgery involving the sacrum or pelvis 297 [1,33] Larger intraoperative blood loss 216 [26,42] 3 1 [ 12,61] Surgery with spinal instrumentation 856 [33,56] 127 [12,24,27,28,58] Previous surgery 52 [10,50] Blood transfusions 752 [56] 6 1 [ 52] ASA classification 856 [33,56] Limited evidence Hypertension 63 [13] Invasiveness index 63 [13] Renal disease 63 [13] Bony or connective tissue neoplasm 193 [1] Skin to lamina distance 24 [35] Thickness of subcutaneous fat 24 [35] Surgical case order Presence of comorbidities 139 [8,26] Preoperative irradiation 8 [14] Exposure to razor shaving 104 [33] Intraoperative administration of a F i O 2 less than 50 % 104 [33] Suboptimal timing of prophylactic antibiotic therapy 56 [40] Pre-/post-operative elevated serum glucose level 56 [40] 6 …”
Section: Discussionmentioning
confidence: 99%
“…The pooled average SSI rate was calculated to be 1.6% (median, 2.8%; range, 0.2%–18.3%) based on 64 cohorts comprising a total of 212,639 patients. Patients who underwent instrumented spinal fusion procedures were evaluated for SSIs in 35 identified studies [6,12,25,28,35,37,39,48,50,61,67,74,77,78,84,85,90,93,97,98,101,112,121,122,126,127,132,134,135,137,148,154,156,160,174]. The pooled average SSI rate was calculated to be 3.8% (median, 4.2%; range, 0.4%–20%) based on 39 cohorts with a total of 28,628 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Lumbar microdiscectomy usually involved a longer incision than usual in obese patients11). Retraction was difficult and visualization of the important elements of the operation was obscured by the patient's depth4). This study was performed to evaluate outcomes after lumbar microdiscectomy in patient who are obese.…”
Section: Discussionmentioning
confidence: 99%